Modification of solid phase red cell adherence assay for the detection of platelet antibodies in patients with thrombocytopenia - Preeyanat Vongchan (2018)
Platelet refractoriness is caused by HLA antibodies and platelet-specific antibodies. Current methods used to detect antiplatelet antibodies have limitations. Solid phase red cell adherence (SPRCA) lacks sensitivity and requires a second assay using chloroquine-treated intact platelets to specify the response due to anti-HLA. We modified SPRCA by using 2 types of antihuman platelet antibodies with different specificities toward platelet lysate and tested samples from 361 patients (69 with unexplained thrombocytopenia and 292 with poor response to platelet transfusions not explicable by alloimmunization or the clinical situation) and 50 from healthy volunteers. Our method compared favorably with platelet suspension direct immunofluorescence. All samples from healthy volunteers were negative; of the samples from the patient population, 240 were positive (147 samples had only antiplatelet and 3 samples had only anti-HLA antibodies). This modified technique had a sensitivity of 98% and a specificity of 91%. © American Society for Clinical Pathology.